Where are the workers? : labor's stories at museums and historic sites - Forrant, Robert, 1947-; Trasciatti, Mary Anne (Working class in American history., 2022)
"The labor movement in the United States is a bulwark of democracy and a driving force for social and economic equality. Yet its stories remain largely unknown to Americans. Robert Forrant and Mary Anne Trasciatti edit a collection of essays focused on nationwide efforts to propel the history of labor and working people into mainstream narratives of US history. In Part One, the contributors concentrate on ways to collect and interpret worker-oriented history for public consumption. Part Two moves from National Park sites to murals to examine the writing and visual representation of labor history. Together, the essayists explore how place-based labor history initiatives promotes understanding of past struggles, creates awareness of present challenges, and supports efforts to build power, expand democracy, and achieve justice for working people. A wide-ranging blueprint for change, Where Are the Workers? shows how working-class perspectives can expand our historical memory and inform and inspire contemporary activism"--